Efektivitas Kampanye Iklan Digital Terhadap Kesadaran Merek dan Niat Beli Konsumen PT Citra Andalas Cabang Surabaya - Moh. Wahib (PUTRA JAWA PUBLISHER, 2024)
This study aims to analyze the effectiveness of digital advertising campaigns on brand awareness and consumer purchase intentions of PT Citra Andalas Surabaya Branch. The research method used is a quantitative approach with a survey of consumers who have been exposed to the company's digital advertising. The independent variables in this study include ad content, frequency of exposure, and visual appeal, while the dependent variables include brand awareness and purchase intention. The results of data analysis show that digital advertising campaigns have a significant positive influence on brand awareness, which directly increases consumer purchase intentions. This study concludes that a well-planned and effective digital advertising strategy can strengthen brand positioning and drive consumer purchasing decisions.